Investigating papillary thyroid cancer risk factors among women living at the central region of Iran: a case–control study - Hamed Ghoshouni; Saeed Hosseini; Akram Ghadiri-Anari; Reyhaneh Azizi; Masoud Rahmanian; Narjes Hazar (BMC Endocrine Disorders)
Abstract Background The etiology of thyroid cancer especially in women in not well recognized in Yazd, at the center of Iran. The aim of present study was to investigate the risk factors of thyroid cancer among women living in this province. Methods The present study was carried out as a case–control study, comprising women diagnosed with papillary thyroid cancer (PTC) as the case group, along with two distinct control groups sourced from different origins (i.e., relatives and non-relatives) between 2020 and 2022. Data pertaining to several risk factors including demographic characteristics, reproductive variables, medical history related to thyroid and non-thyroid ailments, exposure to head and neck radiation, as well as familial cancer history, was collected from all participants. Binary logistic regression was utilized to discover risk and protective factors. Results In present study, 77 individuals participated in the case group, 76 in the relative control group and 72 in the non-relative control group. The history of OCP use and exposure to head and neck radiation were remained in the model as risk factors in all three case‒relative control (OR = 6.65, 95%CI: 2.53‒17.49; P-value < 0.001), case‒non-relative control (OR = 6.32, 95%CI: 2.14‒18.70; P-value = 0.001) and case‒total control comparisons (OR = 6.66, 95%CI: 2.84‒15.64; P-value < 0.001). Conclusion The OCP use as well as exposure to head and neck radiation were determined to be strong or relatively strong risk factors in both case‒relative control and case‒non-relative control comparisons. Consequently, it seems these two factors represent genuine risk factors for papillary thyroid cancer.